2012
DOI: 10.18052/www.scipress.com/bsmass.3.5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hall Currents and Radiation on MHD Free Convective Flow Past a Oscillating Vertical Plate with Oscillatory Plate Temperature in a Porous Medium

Abstract: Combined effects of Hall currents and radiation on an unsteady MHD free convective flow past a vertical flat plate with oscillatory plate temperature in a porous medium have been studied. The governing equations are solved analytically in closed form. The results obtained are presented graphically. It is found that the Hall currents accelerate the fluid velocity components whereas the radiation has a tendency to retard the fluid velocity components. Porosity of the medium has a tendency to enhance the fluid ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The transport andthermal properties of the base fluid are converted by nanoparticles. Bhaskar Chandra Sarkar et al [4] revealed that unsteady primary flow Hall current leads to a decrease in the amplitude of the shear stress. Lee et al [5] experimentally inspected the thermal conductivity performance of dilute nanofluids by a transient hot-wire technique.…”
Section: Introductionmentioning
confidence: 99%
“…The transport andthermal properties of the base fluid are converted by nanoparticles. Bhaskar Chandra Sarkar et al [4] revealed that unsteady primary flow Hall current leads to a decrease in the amplitude of the shear stress. Lee et al [5] experimentally inspected the thermal conductivity performance of dilute nanofluids by a transient hot-wire technique.…”
Section: Introductionmentioning
confidence: 99%
“…Aboeldahab and Elbarbary [6] considered effects of Hall current on MHD free convection flow with heat and mass transfer over a vertical in the presence of a strong external magnetic field. Sarkar et al [7] investigated effects of Hall currents and radiation on MHD free convection flow past an oscillating vertical plate with oscillatory plate temperature in a porous medium.…”
Section: Introductionmentioning
confidence: 99%